NANOG is required to establish the competence for germ-layer differentiation in the basal tetrapod axolotl. - Luke A Simpson; Darren Crowley; Teri Forey; Helena Acosta; Zoltan Ferjentsik; Jodie Chatfield; Alexander Payne; Benjamin S Simpson; Catherine Redwood; James E Dixon; Nadine Holmes; Fei Sang; et al. (PLoS Biology, 2023)
Pluripotency defines the unlimited potential of individual cells of vertebrate embryos, from which all adult somatic cells and germ cells are derived. Understanding how the programming of pluripotency evolved has been obscured in part by a lack of data from lower vertebrates; in model systems such as frogs and zebrafish, the function of the pluripotency genes NANOG and POU5F1 have diverged. Here, we investigated how the axolotl ortholog of NANOG programs pluripotency during development. Axolotl NANOG is absolutely required for gastrulation and germ-layer commitment. We show that in axolotl primitive ectoderm (animal caps; ACs) NANOG and NODAL activity, as well as the epigenetic modifying enzyme DPY30, are required for the mass deposition of H3K4me3 in pluripotent chromatin. We also demonstrate that all 3 protein activities are required for ACs to establish the competency to differentiate toward mesoderm. Our results suggest the ancient function of NANOG may be establishing the competence for lineage differentiation in early cells. These observations provide insights into embryonic development in the tetrapod ancestor from which terrestrial vertebrates evolved.